ESTIMATION OF 3D CARBONATE RESERVOIR PERMEABILITY AND INTERPARTICLE POROSITY BASED ON ROCK TYPES DISTRIBUTION MODEL - Mohammad Syamsu Rosid; Rizky Achmad Kurnia; Mochamad Wahdanadi Haidar (GEOMATE Journal, 2020)
Carbonate reservoir in “R” Oil Field is a reef limestone that has a very complex porosity and permeability characteristics caused by its diverse pore types (interparticle, stiff, and crack). This study aims to characterize the carbonate reservoir by estimating its interparticle porosity and permeability based on rock types distribution model. Modified Rock-Fabric Classification is used to determine the distribution of rock types in three reference wells (R2, R9, R20). Rock Types (RT) distribution model is generated by integrating Acoustic Impedance (AI) and Shear Impedance (SI) attributes from seismic simultaneous inversion with rock types distribution in reference wells using Naïve-Bayes Classifier. Three-dimensional (3D) interparticle porosity and permeability are then estimated from the rock types distribution model. The result shows RT3 which is characterized by crack pores as the most dominant rock type in the reservoir followed by RT5, RT4, and RT6 which are characterized by interparticle pores. Relatively high interparticle porosity values ranges from 0.18 to 0.22 can be associated with RT6 of mud-dominated packstone or wackestone. Meanwhile, relatively high permeability values range from 70 to 80 millidarcy (mD) can be associated with RT4 of grainstone. Laterally, there are clusters of spots in the south of the three reference wells that showed relatively high permeability value.